Pemphigoid gestationis. Case report - La Rotta-Nuñez, Elisabeth (2023)
Xanthogranulomatous inflammation of the female genital tract is infrequent and iseven rarer in fallopian tubes and ovaries. We present a case of xanthogranulomatousoophorosalpingitis in a 45-year-old female patient who consulted for left iliac fossapain accompanied by fever. Bimanual examination revealed a slightly enlarged uteruswith a firm, non-painful left adnexal mass, adherent to the uterus and with limitedmobility. Transvaginal ultrasound evaluation showed a heterogeneous left ovariantumor with thick and irregular walls with multiple septa and internal echoes withoutvisualization of the ovary. During surgery, dense adhesions were found from the massto the pelvic lateral wall, ovarian fossa, and bowel loops. The uterus was displaced bya thick-walled, grayish-white, cystic left adnexal tumor draining foul-smelling purulentfluid. The definitive diagnosis was xanthogranulomatous oophorosalpingitis. Thiscondition is a rare inflammatory process that poses diagnostic dilemmas. Its clinicalmanifestations and imaging features may mimic a malignant pelvic neoplasm, so ahigh index of suspicion is necessary for its diagnosis, as a differential diagnosis inpatients with complex cystic ovarian tumors. Histopathological examination is thegold standard for diagnosis.